2011
DOI: 10.1186/1471-2288-11-146
|View full text |Cite
|
Sign up to set email alerts
|

Validation of diabetes mellitus and hypertension diagnosis in computerized medical records in primary health care

Abstract: BackgroundComputerized Clinical Records, which are incorporated in primary health care practice, have great potential for research. In order to use this information, data quality and reliability must be assessed to prevent compromising the validity of the results.The aim of this study is to validate the diagnosis of hypertension and diabetes mellitus in the computerized clinical records of primary health care, taking the diagnosis criteria established in the most prominently used clinical guidelines as the gol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
68
2
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(80 citation statements)
references
References 29 publications
6
68
2
4
Order By: Relevance
“…For instance, de Burgos-Lunar et al 21 conducted a validation study of diabetes mellitus and hypertension diagnoses in primary health care electronic records and found that both sensitivity and specificity were 99.5% for diabetes and were 85% and 97%, respectively, for hypertension. These results are consistent with our findings (100% sensitivity and 99% specificity for diabetes; 83% sensitivity and 98% specificity for hypertension).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, de Burgos-Lunar et al 21 conducted a validation study of diabetes mellitus and hypertension diagnoses in primary health care electronic records and found that both sensitivity and specificity were 99.5% for diabetes and were 85% and 97%, respectively, for hypertension. These results are consistent with our findings (100% sensitivity and 99% specificity for diabetes; 83% sensitivity and 98% specificity for hypertension).…”
Section: Discussionmentioning
confidence: 99%
“…Insurance status was categorized as private, Medicare, medical assistance/ Medicaid, or self-pay. Comorbidities were determined on the basis of their presence on the patient's problem list, as a billing diagnosis on two outpatient encounters, or active use of a specified medication (Supplemental Table 1) (7,37,(39)(40)(41)(42)(43)(44)(45)(46)(47). The university-affiliated health system mandates that providers enter all prescriptions electronically and maintain an up-to-date medication list.…”
Section: Covariatesmentioning
confidence: 99%
“…HTN was identified on the basis of two outpatient billing diagnoses, a problem list diagnosis, or the use of an antihypertensive medication (37)(38)(39)(41)(42)(43)(44). For patients with a diagnosis of HTN, all recorded office BP values from the cohort period were abstracted from the EHR.…”
Section: Bp Controlmentioning
confidence: 99%
“…Las bases de datos clínico-administrativas como la historia electrónica de AP, que ha demostrado validez para realizar estudios epidemiológicos y de utilización de servicios de salud 4,26,27 , pueden ser un instrumento útil para llevar a cabo estudios comunitarios con pacientes ambulatorios con IC. No obstante, es una fuente de información que junto con la naturaleza observacional del estudio implica asumir diversos sesgos.…”
Section: Discussionunclassified